Group of units of finite group algebras of groups of order 24 - Sahai, M.; Ansari, S. F. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 512.5 Let F be a finite field of characteristic p. The structures of the unit groups of group algebras over F of the three groups D_24, S_4 and SL(2, Z_3) of order 24 are completely described in numerous works. We present the unit groups of the group algebras over F for the remaining groups of order 24, namely, C_24, C_12 × C_2, C_2^3 × C_3, C_3 times C_8, C_3 times Q_8, D_6 × C_4, C_6 times C_4, C_3 times D_8, C_3 × D_8, C_3 × Q_8, A_4 × C_2, and D_12 × C_2.